Adsorption Isotherms of Benzene and Its Derivatives by RPLC Frontal Analysis - WAN, XIAOLONG; CHOI, DAE-KI; HO ROW, KYUNG (Asian Journal of Chemistry, 2010)
The adsorption behaviour of solute is one of the most important factors to design a batch and a continuous liquid chromatographic separation process. In liquid chromatography, these behaviours are based on the adsorption equilibrium between a liquid mobile-phase and a solid stationary-phase. However, almost of the retention models were developed under linear adsorption isotherm only few researchers have investigated the relationship between the adsorption parameters and the mobile phase composition and some empirical models were introduced. In this work, the adsorption isotherms were obtained by the frontal analysis for 4 low-molecular compounds (benzene, toluene, chlorobenzene and 1,2- dichlorobenzene) on a commercial C18 bonded column. The absorption based on the linear and Langmuir models was investigated according to the changes of the composition of methanol high-enriched eluent. The calculations and analysis of the coefficients obtained for both models confirm that the adsorption data for solutes are best modeled with the linear approach. Langmuir isotherm model couldn't satisfactorily describe mechanism and provide the objective information on the physical nature of the absorption in spite of the acceptable accuracy.